Cultural adaptation of a community‐based advance serious illness planning decision aid to the Quebec context involving end‐users - Ariane Plaisance; Yoanna Skrobik; Mathieu Moreau; Felix Pageau; Diane Tapp; Daren K. Heyland (Wiley, 2022)
Abstract Introduction Traditional advance care planning focuses on end‐of‐life planning in the context of a certain or imminent death. It is not tailored for serious illness planning, where the 'death' outcome is uncertain. The Plan Well Guide™ (PWG) is a decision aid that empowers lay persons to better understand different types of care and prepares them, and their substitute decision‐makers, to express both their authentic values and informed treatment preferences in anticipation of serious illness. A cultural adaptation was necessary to make the material suitable to the context of Quebec, a French‐speaking Canadian province. Methods We engaged lay collaborators and experts in a panel, involving three phases of consultation and data collection. These included an online questionnaire, focused interviews and virtual focus groups that identified elements within the francophone PWG affecting its feasibility, adaptation and integration, as well as items that should be modified. Results We engaged 22 collaborators between April and September 2021. The majority (82%) ranked the first translation as good or very good; most (70%) stated that they would recommend the final adaptation. Both lay and expert panel members suggested simplifying the language and framing the tool better within the context of other advance medical planning processes in Quebec. Translation was considered in a cultural context; the challenges identified by the research team or by collaborators were addressed during the focus group. Examples of wording that required discussion include translating 'getting the medical care that's right for you' when referring to the PWG's goal. An equivalent expression in the French translation was believed to invoke religious associations. Using the term 'machines' to describe life‐sustaining treatments was also deliberated. Conclusion Our collaborative iterative adaptation process led to the first French advanced serious illness planning tool. How acceptable and user‐friendly this French adaptation of the PWG is in various Canadian French‐speaking environments requires further study. Contribution We organized a focus group inviting both lay collaborators and experts to contribute to the interpretation of the results of the previous phases. This choice allowed us to add more value to our results and to the final PWG in French.